The Influence of Soviet Law on the 1959 Vietnamese Constitution - Thinh, Phan Quang (VNU Journal of Science: Legal Studies; Vol 40 No 1, 2024)
The impact of the Soviet legal culture, particularly on Vietnam, within the socialist bloc, stands as a notable assertion. The incorporation of Soviet legal constructs into Vietnam’s legal framework emerged as a vital political necessity during a complex phase of Vietnam’s historical trajectory. Illustrated prominently in the 1959 Constitution of the Democratic Republic of Vietnam, this influence embodies a quintessential manifestation of Soviet legal impact on Vietnam. This paper delves into several facets of this influence, encompassing the Constitutional structure, articulation of citizenship rights and duties, confirmation of the Vietnamese Labour Party (now the Communist Party of Vietnam) leadership, configuration of State apparatus and power distribution, formulation of socioeconomic order, and a departure from Western constitutional paradigms. The inquiry primarily draws upon historical and comparative legal methods. Legal records from Vietnam and the Soviet Union have been amassed, scrutinized, and likened. Moreover, this study considers the legal and interdisciplinary insights offered by scholars from Vietnam, the Soviet Union, Russia, and the Western sphere pertaining to the subject matter of this article. These perspectives are not only considered but also assessed and integrated. The outcomes of this examination serve to elucidate: i) the significance of Vietnam’s 1959 Constitution in the progression of Vietnam’s socialist legal system; ii) the historical connection and contemporary inheritance of shared legacies between the two national legal systems within the overarching socialist legal framework; and iii) valuable insights into incorporating socialist legal norms into the constitutional process. Tra từ & tra câu Anh - Việt, Việt - Anh, Anh - Anh     Nhúng biểu tượng tra cứu vào trang Nhấp đúp để tra cứu